Nurse’s Characteristics as a Leader in Emergency Settings: a Bibliographic Review - Reis, Joana; Dias, Débora; Nunes, Nísia; Ruxa, Sara (Salud Integral y Comunitaria, 2026)
Introduction: The nurse’s leadership in emergency settings plays a crucial role in the efficiency and safety of care provision, where swift and critical decisions in unstable environments are required. The nurse’s ability to lead teams, coordinate resources, and ensure the quality of care can be decisive in guaranteeing favorable outcomes for both team and patients. Objective: To identify and synthesize evidence on the nurse’s characteristics as a leader in emergency settings. Methods: A rapid review following the Cochrane methodology. A search was conducted in two databases: CINAHL Complete and MEDLINE Complete. The methodological quality assessment and risk of bias for the selected studies were conducted using the Joanna Briggs Institute’s critical appraisal tools. The results from the studies were summarized narratively. Results: Three articles were selected. The nurse’s characteristics as a leader in emergency settings were synthesized into three key domains: intellectual, encompassing knowledge and cognitive skills; technical, related to clinical and procedural expertise; and relational, with a strong emphasis on effective communication, the most frequently cited attribute. Conclusions: This review’s findings provide a foundational reference for future research, underscoring the need for further primary studies to expand and deepen the understanding of nursing leadership in emergency settings.